Intrigo internazionale a Modena. La causa di Crouy-Chanel contro Francesco V tra alta politica, nazionalismo e massoneria - Attolini, Alberto (Verbum – Analecta Neolatina, 2022)
In the aftermath of the fall of the ducal government of Modena, Baron Albert Nyáry was among the first to study the documents of the Este archives, which had recently been opened to the public. This research activity achieved as a result the printing of two pamphlets of a historical-genealogical nature, which became the starting point for a particular court case: Auguste Crouy-Chanel sues Francis V to claim the title of Duke of Modena. What, at first glance, might appear to be little more than a bizarre controversy with no legal basis, is put back into its original context of Hungarian political emigration circles and Masonic lodges, ending up revealing an underlying plot of international politics conceived in France and aimed at striking at the Empire of Austria and the House of Habsburg.